Single nucleotide polymorphisms in common bean : Their discovery and genotyping using a multiplex detection system - Gaitán Solís, Eliana; Choi, I.Y.; Quigley, C; Cregan, P.B.; Tohme, Joseph M. (Wiley, 2008)
Single nucleotide polymorphism (SNP) markers are by far the most common form of DNA polymorphism in a genome. The objectives of this study were to discover SNPs in common bean (Phaseolus vulgaris L.) by comparing sequences from coding and noncoding regions obtained from the GenBank and genomic DNA and to compare sequencing results with those obtained using single base extension (SBE) assays on the Luminex-100 system for use in high-throughput germplasm evaluation. We assessed the frequency of SNPs in 47 fragments of common bean DNA, using SBE as the evaluation methodology. We conducted a sequence analysis of 10 genotypes of cultivated and wild beans belonging to the Mesoamerican and Andean genetic pools of P. vulgaris. For the 10 genotypes evaluated, a total of 20,964 bp of sequence were analyzed in each genotype and compared, resulting in the discovery of 239 SNPs and 133 InDels, giving an average SNP frequency of one per 88 bp and an InDel frequency of one per 157 bp. This is the equivalent of a nucleotide diversity (?) of 6.27 × 10?3. Comparisons with the SNP genotypes previously obtained by direct sequencing showed that the SBE assays on the Luminex-100 were accurate, with 2.5% being miscalled and 1% showing no signal. These results indicate that the Luminex-100 provides a high-throughput system that can be used to analyze SNPs in large samples of genotypes both for purposes of assessing diversity and also for mapping studies.